High‐order high‐performance LCLCL DC/DC converter based on harmonic optimisation. Issue 14 (1st November 2020) - Zhang, Xiangjun; Dai, Mingcong; Guan, Yueshi
Abstract : This work presents a new type of high‐order LCLCL resonant DC/DC converter. The converter in this study can properly inject the third harmonic for energy transmission through optimal configuration and parameter design of the resonant tank, which can not only achieve a wider voltage regulation range but also provide an easy method for soft start and overcurrent protection. In this study, both switches can realise soft switching, and due to the injection of the third harmonic, the loss of the secondary rectifier diode is reduced. This article describes the working principle of the LCLCL converter and provides the parameter design principle and small‐signal modelling method. In the laboratory, a 400 W prototype with 400 V input and 24 V output is built to verify the correctness of the theoretical analysis.